Stroke as a neurological complication of COVID-19 (Research, Society and Development, 2021)
Objective: To analyze stroke as a complication caused by COVID-19, as well as its clinical repercussions. Methodology: This is an integrative review of articles containing information on diagnoses of neurological signs and symptoms. The search for scientific articles was carried out in the following databases: Latin American and Caribbean Literature on Health Sciences (LILACS), SCIENCE DIRECT, Medical Literature Analysis and Retrieval System Online (MEDLINE) and Scientific Electronic Library Online (SCIELO). Results: Seven articles were selected to perform the integrative review. All manuscripts were published in 2020 (100%). Information was collected regarding the authors, country, title, objective and results found in the studies, elaborating discussions about each article. On the other hand, the authors show that SARS-CoV-2 affects far beyond the lungs and is more than a flu syndrome, demonstrating a multisystemic character, regardless of gender, age and chronic comorbidities. Conclusion: The review showed that there is a tendency that hospitalized patients with severe symptoms of COVID-19 are more likely to develop neurological problems such as a veactually. However, more studies are needed to contain a higher quality of evidence, as well as that health professionals make a broader diagnosis capable of covering all signs and symptoms present in patients with coronavirus.